Pengembangan Modul Ajar berbasis STEAM-Inkuiri untuk Meningkatkan Minat Belajar dan Keterampilan Berpikir Kritis Peserta Didik di SMK Kesehatan Nusantara Palu - Farhana Lembah; Achmad Ramadhan; Sutrisnawati (Jurnal Pendidikan Indonesia, 2026)
Learning in vocational high schools (SMK) in the health field still faces limitations in contextual and interactive teaching materials, which negatively affect students’ learning interest and critical thinking skills, particularly in Human Anatomy and Physiology topics. This study aimed to develop, validate, and evaluate a STEAM–Inquiry-based learning module to enhance students’ learning interest and critical thinking skills in health vocational schools. The study employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, and Disseminate), which was limited to the Develop stage. The research subjects consisted of 29 eleventh-grade students selected through purposive sampling. The research instruments included a critical thinking skills rubric, a learning interest questionnaire, and expert validation sheets. Data were analyzed using descriptive statistics and N-Gain tests. The results indicated that the STEAM–Inquiry-based module achieved a very high feasibility level (>76%) and significantly improved students’ learning interest and critical thinking skills, with an N-Gain score of 0.71. The module was found to be valid, practical, and effective in promoting active, creative, and critical learning. The implications of this study suggest that the STEAM–Inquiry-based module can serve as an innovative alternative teaching material in health vocational schools to support the implementation of the Merdeka Curriculum and to strengthen 21st-century learning oriented toward critical thinking and problem-solving skills.